Teachers’ qualifications and students’ academic performance in biology in senior secondary schools in Benue State, Nigeria - Helen, Aladi; Angura, Michael Terfa; Omaga, Joy Okache; Nyinebi, Ochanya Maryrose (American Journal of Education and Learning, 2025)
The study examined the relationship between biology teachers’ qualifications and students’ academic performance in biology in public and private senior secondary schools in Benue State, Nigeria. A descriptive correlational survey design was used for the study. Three research questions and three hypotheses guided the study. The population comprised biology teachers and students in government-approved public and private schools in Benue State. The sample consisted of 100 teachers and 200 students randomly selected from 50 senior secondary schools (25 public schools and 25 private schools, respectively) using purposive sampling technique. The Biology Teachers Qualification Checklist (BTQC) and past examination results of students in biology were used for data collection. The data collected were analyzed using percentages, independent t-tests, and Pearson Product Moment Correlation (PPMC). The findings revealed that the difference between the percentage of qualified biology teachers in public and private secondary schools is statistically significant in favor of biology teachers in public senior secondary schools (t = 0.055, P < 0.005). It was also found that there is a significant relationship between teachers’ qualifications and students’ academic performance in biology in both public (r = 0.899, P < 0.005) and private senior secondary schools (r = 0.794, P < 0.005). The study recommended, among other things, that the state ministry of education and all stakeholders should ensure that, irrespective of the school’s status, qualified biology teachers are available to cover the syllabus, and regular workshops should be organized for biology teachers to enhance their competence levels to improve students’ academic performance.